Reverse Time Migration: A Seismic Imaging Technique Applied to Synthetic Ultrasonic Data. (5th July 2012) - Müller, Sabine; Niederleithinger, Ernst; Bohlen, Thomas
Abstract : Ultrasonic echo testing is a more and more frequently used technique in civil engineering to investigate concrete building elements, to measure thickness as well as to locate and characterise built-in components or inhomogeneities. Currently the Synthetic Aperture Focusing Technique (SAFT), which is closely related to Kirchhoff migration, is used in most cases for imaging. However, this method is known to have difficulties to image steeply dipping interfaces as well as lower boundaries of tubes, voids or similar objects. We have transferred a processing technique from geophysics, the Reverse Time Migration (RTM) method, to improve the imaging of complicated geometries. By using the information from wide angle reflections as well as from multiple events there are fewer limitations compared to SAFT. As a drawback the required computing power is significantly higher compared to the techniques currently used. Synthetic experiments have been performed on polyamide and concrete specimens to show the improvements compared to SAFT. We have been able to image vertical interfaces of step-like structures as well as the lower boundaries of circular objects. It has been shown that RTM is a step forward for ultrasonic testing in civil engineering.